Einstein observations and the internal dynamics of compact stars: further evidence against non-linear regimes of vortex creep - Horvath, Jorge Ernesto (1991)
Structural constraints are presented on the Crab and Vela pulsars imposed by the simultaneous assumptions of (a) surface temperatures close to those observed by the Einstein Observatory satellite, and (b) validity of the vortex creep theory in the nonlinear regime for interpreting glitch observations and internal features predicted by it. The disagreement between both studies is quantified, thus pointing strongly to the need for linear regimes of creep, as recently suggested, or some alternative picture